Psychosocial Determinants of Quality of Life in Patients with Type 2 Diabetes Mellitus: A Scoping Review - Januarso Setiawan; Fadli delian Pangaribawa; Besar Tirto Husodo (Universitas Ahmad Dahlan, 2026)
Psychosocial factors, particularly perceived social support, are increasingly recognised as important determinants of quality of life (QoL) among adults with Type 2 Diabetes Mellitus (T2DM). This scoping review mapped the breadth, nature, and distribution of evidence regarding psychosocial determinants associated with QoL in T2DM, following Arksey and O'Malley’s six-stage framework as updated by Peters et al., and reported in accordance with the PRISMA-ScR guidelines. Four electronic databases (PubMed, Scopus, PsycINFO, and Google Scholar) were systematically searched for peer-reviewed studies published between 2019 and 2025, resulting in 28 eligible studies from 847 initial records. To contextualise the review findings, a supplementary cross-sectional study involving 180 outpatients with T2DM in Central Java, Indonesia, was conducted. Thematic synthesis identified three overarching domains influencing QoL: glycemic-functional burden, psychosocial buffering, and cumulative chronicity. Across the reviewed evidence and the supplementary cohort, poor glycemic control (HbA1c ≥8%) consistently emerged as the strongest negative predictor of QoL (β = −0.362, p < .001), whereas perceived social support was the strongest positive predictor (β = 0.318, p < .001). Critical appraisal using the Mixed Methods Appraisal Tool (MMAT) indicated predominantly moderate-to-high methodological quality across included studies. The findings underscore the importance of integrating psychosocial screening and support into routine diabetes care, particularly in collectivist healthcare contexts where family and community support play central roles in chronic disease management.